MODEL PENILAIAN KEMAMPUAN BERPIKIR HISTORIS (HISTORICAL THINKING) DENGAN MODEL RASCH - Ofianto, Ofianto; Basri, Wahidul (TINGKAP, 2015)
This study was conducted to produce a model and instruments of historical thinking skills in the history subject at the senior high school (SHS) and to identify SHS students’ historical thinking skills. The study was conducted in two stages, i.e. model development and instrument development along with a small-scale tryout and a large-scale tryout. The test for each tryout consisted of six and five sub-test sets. Each test set contained 20 anchor items. The sample for each tryout comprised 1573 and 2613 testees. The data were analyzed by means of Partial Credit Model (PCM) using the QUEST program. The tryout results on whole indicated that based on the criteria for an INFIT MNSQ mean of 1.0 and a standard deviation of 0.0 the tests fitted PCM. The reliability coefficients of the tests for the tryouts were moderately good; the Cronbach’s alpha coefficients were, respectively, 0.65 and 0.54. The lowest score of historical thinking skills was -.352 and the highest was +1.21 in an ideal range of -4.0 to +4.0. On the whole, the testees’ scores were not satisfactory. Only 5.89% of the testees were above the expected median. Keywords: Instrument development, test, historical thinking skills, polytomous, PCM